Hematological, biochemical and ruminant parameters for diagnosis of left displacement of the abomasum in dairy cows from Southern Brazil - Cardoso, Felipe Cardoso de; Esteves, Vanessa Sinnott; Oliveira, Simone Tostes de; Lasta, Camila Serina; Valle, Stella Faria; Campos, Rómulo; González, Félix Hilario Diaz (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate hematological, biochemical and ruminant parameters for diagnosis and treatment of the left displaced abomasum (LDA) in dairy cows, in the Plateau Region of Rio Grande do Sul, Brazil. Ruminant fluid, blood and urine samples were collected from 20 cows suffering LDA and from 20 healthy cows (control). The cows with LDA showed lower values of daily milk production, body weight and corporal condition score. The use of pH reagent strips showed to be functional in the field, when compared to a digital pH meter. Ruminant dynamics was damaged in cows affected by LDA, as it was evidenced by the higher reduction time of methylene blue. Serum values of lactate, beta-hydroxybutyrate, urea, albumin, free fatty acids and cholesterol shows to be auxiliary tools in the LDA characterization.